Higher cough flow is associated with lower risk of pneumonia in acute stroke. Issue 5 (1st February 2016) - Kulnik, Stefan T; Birring, Surinder S; Hodsoll, John; Moxham, John; Rafferty, Gerrard F; Kalra, Lalit
Abstract : There is little available evidence to demonstrate how cough strength mediates the risk of aspiration-related pneumonia in acute stroke. Our secondary analysis of trial data indicates that risk of pneumonia reduces with increasing peak cough flow (PCF) of voluntary cough (OR 0.994 for each 1 L/min increase in PCF, 95% CI 0.988 to 1.0, p=0.035); and to a lesser degree with increasing PCF of reflex cough (OR 0.998 for each 1 L/min increase in PCF, 95% CI 0.992 to 1.004, p=0.475). These data serve hypothesis generation. Further studies are needed to confirm these findings and validate their clinical utility. Clinical trial registration number: ISRCTN40298220 (post-results).